Implementation of REBT Group Counseling to Overcome the Confidence Crisis - Bunga Nurriska Fitri; Ikke Ratna Sari; Khoirunniswah; Yenita Putri Widyaningrum (Penerbit Hellow Pustaka, 2024)
The latest fashion trends are a complement for students, where students are known to be surrounded by people who really pay attention to appearance or fashion, sometimes this appearance also causes pressure on themselves due to the outfits they wear every day. The purpose of this counseling activity is to find out how much influence outfits have on the self-confidence of each education student who has his own rules for dressing. This counseling focuses on implementing group counseling services to overcome self-confidence problems in students using REBT group counseling techniques. In implementing activities, this service focuses on the effectiveness of REBT group counseling in increasing students' self-confidence by collecting data using questionnaires. This method is very effective in increasing students' low self-confidence. Barriers to implementing group counseling are various student perceptions of group counseling.